Strategi Komunikasi dalam Peningkatan Citra Positif Melalui Program Corporate Social Responsibility (CSR) pada KSPPS Abdi Kerta Raharja - Suminah Suminah; Eka Susilawati; Fithrotul Kamilah; April Laksana; Arfian Suryasuciramdhan (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study analyzes the communication methods used by the Sharia Savings and Loan and Financing Cooperative (KSPPS) Abdi Kerta Raharja to increase a positive image through the Corporate Social Responsibility (CSR) program in the ZISWAF division. The primary focus is on how effectively the CSR program’s messages are delivered and how they contribute to building trust and fostering good relationships with the community. A qualitative research method with a descriptive approach was employed, involving data collection through in-depth interviews, observations, and literature studies. The findings indicate that KSPPS Abdi Kerta Raharja has successfully implemented various CSR initiatives designed to empower the community and enhance welfare, which, in turn, has contributed to a positive image of the cooperative in the eyes of the public. Furthermore, the study examines how the community perceives and responds to these programs, how information is disseminated through media, and the impact on member loyalty. This research highlights the significance of communication in ensuring the effectiveness of CSR efforts and the strengthening of community ties. The results are expected to provide insights for KSPPS managers to develop improved and sustainable communication strategies that will help foster a positive image and further the success of CSR programs in the future.